Analysis of the Arabic Language Textbook Syahid Wa Ta'allam Li al-NÄthiqÄ«n BighairihÄ by Hassan Muhammad Abdel Maqsoud According to Amani and Awatifâ€™s Theory: ØªØÙ„ÙŠÙ„ ÙƒØªØ§Ø¨ Ø´Ø§Ù‡Ø¯ ÙˆØªØ¹Ù„Ù… Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ Ù„ØØ³Ù† Ù…ØÙ…Ø¯ Ø¹Ø¨Ø¯ Ø§Ù„Ù…Ù‚ØµÙˆØ¯ Ø¹Ù„Ù‰ Ù†Ø¸Ø±ÙŠØ© Ø£Ù…Ø§Ù†ÙŠ ÙˆØ¹ÙˆØ§Ø·Ù - Alfatawi, Ahmad Talkhis; Taufiq, Mirwan Akhmad (STUDI ARAB, 2023)
This study aims to determine quality textbook Syahid Wa Ta'allam Li al-Nathiqin Bighairiha. This study uses the method descriptive qualitative with type of research is library research. The main data source of this research is sourced from textbooks Syahid Wa Ta'allam Li al-Nathiqin Bighairiha compiled by Hasan Muhammad Abdul maqsud lecturer at Ain Syams University, Cairo, Egypt. Collection of research data with techniques documentation in depth literature review and then analyze it. Based on analysis, the researcher have found this book was included in the category of good textbooks. But, from some existing assessment. The book Syahid Wa Ta'allam Li al-Nathiqin Bighairiha are some deficianicies that need to be improved, such as covers are less attractive to students, not keep up with the times and development.